2020
DOI: 10.12968/johv.2020.8.8.338
|View full text |Cite
|
Sign up to set email alerts
|

What is school readiness? A qualitative exploration of parental perceptions in England

Abstract: School readiness is a strong predictor of educational attainment and future health, but its meaning to parents is uncertain. This study aimed to generate an understanding of how parents conceptualise school readiness, and the forms of support they would find most acceptable and effective. Semi-structured interviews were undertaken with 17 parents and were analysed thematically. Parents appeared conflicted in their beliefs about the most important school readiness factors (physical, social and emotional health)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Secondly, the impact of family socioeconomic status on parenting and child education practices emphasizes the role of socioeconomic factors in shaping parenting styles across different social groups. These results are consistent with earlier studies, including (Davies et al, 2020;Ndijuye, 2023;Puccioni et al, 2019), which found that a child's socioeconomic status significantly affects their level of achievement. Socioeconomic status determines the available infrastructure and resources and influences parental engagement in their children's education, influenced by their own educational backgrounds.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, the impact of family socioeconomic status on parenting and child education practices emphasizes the role of socioeconomic factors in shaping parenting styles across different social groups. These results are consistent with earlier studies, including (Davies et al, 2020;Ndijuye, 2023;Puccioni et al, 2019), which found that a child's socioeconomic status significantly affects their level of achievement. Socioeconomic status determines the available infrastructure and resources and influences parental engagement in their children's education, influenced by their own educational backgrounds.…”
Section: Discussionsupporting
confidence: 93%
“…This recognition and promotion of cognitive school readiness (SR) as an important aspect of childhood education is crucial as it helps establish important developmental foundations desired for children to acquire more complex skills as they progress in life. Studies have established that children with high cognitive SR are better-prepared to perform better in life compared to children with poor cognitive SR (Blair & Raver, 2015;Davies et al, 2020).…”
Section: Introductionmentioning
confidence: 99%